2012
DOI: 10.1016/j.rppnen.2012.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Sedation with midazolam in flexible bronchoscopy – A prospective study

Abstract: ResumoIntrodução: Os agentes sedativos têm vindo a ser cada vez mais utilizados na broncofibroscopia (BF) para melhorar o conforto do doente. Devido à sua rápida ação, propriedades ansiolíticas e amnésicas, o midazolam é um dos sedativos mais frequentemente usados. Objetivos: Avaliar o efeito da sedação com midazolam na BF, incluindo a tolerância do doente, complicações e a sua potencial aplicação na prática clínica diária. Material e métodos: Estudo multicêntrico, prospetivo, randomizado, controlado com place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 17 publications
(18 reference statements)
1
16
1
1
Order By: Relevance
“…Group II had high five points FOI scores reflecting better patient tolerance in group I. These findings were similar to that of a study by Rodrigues AJ et al, Rolo R et al and Dhasmana S et al who documented that midazolam and fentanyl, provide better intubating circumstances, patient comfort and tolerance in fiberoptic bronchoscopy [21][22][23]. In our study, improved conditions were observed using dexmedetomidine due to its analgesic and sedative effects [24].…”
Section: Discussionsupporting
confidence: 91%
“…Group II had high five points FOI scores reflecting better patient tolerance in group I. These findings were similar to that of a study by Rodrigues AJ et al, Rolo R et al and Dhasmana S et al who documented that midazolam and fentanyl, provide better intubating circumstances, patient comfort and tolerance in fiberoptic bronchoscopy [21][22][23]. In our study, improved conditions were observed using dexmedetomidine due to its analgesic and sedative effects [24].…”
Section: Discussionsupporting
confidence: 91%
“…[18]. In a recent randomised controlled trial, ROLO et al [7] showed that patients sedated with midazolam had less cough and dyspnoea and had increased patient-reported comfort and willingness to have a repeat procedure compared with placebo. This has been previously shown by others, such as CASES VIEDMA et al [40] who also showed that the use of midazolam, reduced operator difficulties in performing the procedure and procedure time.…”
Section: Benzodiazepinesmentioning
confidence: 99%
“…Another study showed that with the proper patient selection, awake bronchoscopy is well tolerated [2]. However, the majority of physicians now use pharmacological sedatives [3] and anxiolytics, improving procedural tolerance and patient satisfaction, as shown by several case-control studies and randomised controlled trials [4][5][6][7][8]. There is no standardised practice for the use of sedation in bronchoscopy with a good deal of variation among physicians regarding the use of pre-procedure medication and pharmacological sedatives [3,9].…”
mentioning
confidence: 99%
“…1 International guidelines recommend a midazolam dose ranging from 0.06 to 0.07 mg/kg. 9 Therefore, to address this uncertainty, in our randomized, placebo-controlled, dose-finding study, we evaluated whether midazolam premedication improves (a) patient-reported tolerance; and (b) physician evaluation of the feasibility and completeness of a flexible bronchoscopic procedure. [2][3][4] Indeed, the evidence supporting the use of sedation in flexible bronchoscopy is mostly derived from 2 open-label placebo-uncontrolled studies 5,6 showing that sedation had a beneficial effect on the patient-reported tolerance of the procedure.…”
mentioning
confidence: 99%